El tiempo y el lugar de los peces : saberes asociados a la pesca en Puerto César, golfo de Urabá (2014)
ABSTRACT: This article describes the knowledge of a community of artisanal fishermen established in the village of Puerto César in the gulf of Urabá. It highlights the importance of fishing knowledge categories such as weather and climate, and their inﬂuence over the fishes’ migrations and behaviors as key elements to a successful catch. The study reveals how local knowledge together with ideas of nature and the socio-economic situation in which ﬁshermen live, inﬂuences the different perspectives they assume regarding the state of resources and the conservation strategies to protect them.